Baby Weight And Length Based On Arduino Uno With Combination Of Ultrasonic Sensor Hc-Sr04 And Weight Sensor (Load Cell) - Sujiwa, Akbar; Marta, Bayu Tirta; Afif Nuril Musthofa (Universitas PGRI Adi Buana Surabaya, 2024)
Infant development and growth at the age of 0 to 1 year. Babies are easily affected by malnutrition or, if parents ignore the development and growth of the baby. Generally, parents will take their babies to Posyandu or Midwives to have their weight weighed and the length of the baby's body measured. At the time of measuring the baby's body weight and length still using separate and manual measurements. Therefore we need a weighing device that is able to measure the baby's weight and baby's length simultaneously. Then an